CHARACTERISTICS OF CORPORATE GOVERNANCE AND SUSTAINABILITY REPORTING WITH PROFITABILITY AS MODERATING - Wiwi Idawati (Sampoerna University, 2025)
The information disclosed through the company's Sustainability Reporting report transparently will make it easier for stakeholders to know how the company carries out its activities and find out what impacts actually occur in the environment around the Company.This study examines the influence of Corporate Governance, Sustainability Report Disclosure moderated with profitability variables. This study uses data on 34 companies that participated in the Asia Sustainability Reporting Rating for the 2019-2023 period with secondary analysis using quantitative methods. This study examines the influence of Corporate Governance, Sustainability Report Disclosure moderated with profitability variables. This study uses data on 34 companies that participated in the Asia Sustainability Reporting Rating for the 2019-2023 period with secondary analysis using quantitative methods. The results of this study explain that the Audit Committee has no effect on Sustainability Report Disclosure, the Board of Commissioners has a positive effect on Sustainability Report Disclosure, the Board of Directors has a positive effect on Sustainability Report Disclosure, then profitability strengthens the relationship between the Audit Committee and the board of commissioners towards Sustainability Report Disclosure while profitability does not moderate the board of directors towards Sustainability Report Disclosure